Italian companies in England (13th-15th centuries) - SAPORI, A. (PSL Quarterly Review, 2014)
The article examines a phase of special importance in the history of the Italian Mediaeval Companies: that of the work they started in England about the middle of the 13th century and which developed in three directions - the purchase and export of wool, the collection of the papal tithes, and the concession of loans to the Crown - in connection with the policies of the English Kingdom and the financial system of the Church. The most eminent among the companies - the Peruzzi, the Frescobaldi, the Bardi, the Riccardi - succeeded in acquiring a front-rank position at the court of the English Kings, and built up international financial organisations geared on a complicated and risky game of clearings between their several European branches. With like impartiality the author holds up to admiration the enterprise and ability of the individual Companies and at the same time underlines the intrinsic weakness of their daring constructions, which share, with the adverse political events, the responsibility for the famous failures that gave rise to so many emotional recriminations void of historical foundation. JEL: N83